ADVERTISING OF MEDICINES FOR HUMAN USE. PERSPECTIVES FROM EUROPEAN COURT OF JUSTICE - Apan, Rodica Diana (International Journal of Legal and Social Order, 2021)
The present study aims, in the reflection of a decision given by the European Court of Justice to analyze the way to (re) establish the protection of persons in online sales of medicines, both against excessive consumption of medicines generated by advertising, self-medication and the harmful effects of long-term medication not adapted to the person's health. This method is found in the French Consumer Code and is a real connection between the requirements of the pharmacist profession and the requirements of public health protection. Given that a similar protection measure is not included in our legislation, the French regulation would be a good model for a proposal of lege ferenda in the matter.During the Conference "Public safety and the need for high social capital", panel VII, "Protection of human capital in the field of the right to health and social care" was organized, and this study aims to raise the protection of human capital, through rules and jurisprudence which gives efficiency to the concept of "public health". Or, the protection of the population through regulations regarding the distribution of medicines is part of this broad concept.